Smart Advertising: Innovación y disrupción tecnológica asociadas a la IA en el ecosistema publicitario. - Martínez, Inmaculada José Martínez; Terrón, Juan Miguel Aguado; Cobarro, Paloma del Henar Sánchez (Revista Latina de Comunicación Social, 2022)
Introduction: The impact of artificial intelligence (AI) in media industries has received increasing attention in recent years. Research literature in this regard has focused on content production and distribution sectors, leaving advertising in a discreet background. This article aims to take the study of AI and advertising to the forefront, identifying the scope of current research on the subject and offering a map of the research trends, drawing them as a key vector of technology-based innovation in the media ecosystem. Methodology: In order to do so, a qualitative scoping review of the current research literature on AI and advertising has been developed, completed by the contribution of professional reports from the sector. Results and discussion: The existing literature points to the efficiency in large unstructured data sets processing, predictive / prescriptive analysis, natural language recognition and image recognition, as automation as the main AI innovation vectors. The disruptive impact of AI affects all phases of the advertising process: market research and analysis, creativity, media planning and buying, and effectiveness evaluation. Conclusions: Research tends to perpetuate the traditional structure of the advertising process and obviates the ecosystem dimension of innovation, which transforms actors and their relationships.